Influence of the dimple cross-sectional profile on the behavior of gas parallel slider bearings - Liu, Xiang; Li, Xuanqi; Yang, Chunjie; Kang, Hongbo; Zhai, Zhibo; Cui, Yuhao; Qi, Wenjie; Han, Binhui; Liu, Fuxi (Frontiers in Mechanical Engineering, 2024)
This paper studies the effect of the dimple cross-sectional profile on the behavior of gas parallel slider bearings using the numerical method. The numerical method is performed in MATLAB software. The influence of geometrical parameters of dimples on the dimensionless average pressure is studied for different dimple cross-sectional profiles. The geometrical parameters of dimples include dimple depth, dimple area density, transversal textured ratio, and longitudinal textured ratio. It is found that the hydrodynamic lubrication of dimple-textured gas parallel slider bearings is controlled by the dimple depth, dimple area density, transversal textured ratio, longitudinal textured ratio, and dimple cross-sectional profile. Furthermore, the impact of sliding speed on the hydrodynamic lubrication is studied for different dimple cross-sectional profiles. The results indicate that the optimum sliding speed for maximizing the hydrodynamic pressure is controlled by the dimple cross-sectional profile.